(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Nature has always blessed humanity with numerous means of remedy for treating a wide range of diseases. Since different parts of Calamus rotang L. have several ethnopharmacological activities, including CNS depressant and anthelmintic action, its crude methanol extract of leaves was used to investigate its anxiolytic, cytotoxic, and anthelmintic activities. The methanol was selected because it could extract a vast range of phytoconstituents. The anti-anxiety activities of CRME were investigated on the Swiss albino mice model through a hole board and elevated plus maze test, while the cytotoxic and anthelmintic activities were screened on brine shrimps and Pheretima posthuma, respectively. The current study exhibited that crude methanol extract of C. rotang L. leaves had a significant (p>0.001) and dose-dependent effect against anxiety on mice model of hole board and elevated plus maze when compared with that of control. Furthermore, crude methanol extract of C. rotang L. leaves showed a concentration-dependent mild anthelmintic effect exhibiting no cytotoxicity (LC50 value of 1.02 mg/ml). Thus, the present study revealed the potential of crude methanol extract of C. rotang L. leaves as an excellent anxiolytic agent having a mild anthelmintic effect with no cytotoxicity. Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 19-26, 2024